THE IMPLEMENTATION OF COOPERATIVE LEARNING THINK PAIR SHARE STRATEGY IN TEACHING READING COMPREHENSION AT JUNIOR HIGH SCHOOL - Maulizan Z. A.; M. Nur Hakim (IJLECR (International Journal of Language Education and Cultural Review), 2018)
This study aimed to know the implementation of Cooperative learning Think Pair Share Strategy and students' response to teaching reading comprehension at SMP Negeri 1 Bandar Baru. This study used survey method with a qualitative approach. A qualitative research sample was not taken at random but instead, have to follow certain criteria. The Implementation of Think Pair Share strategy was in accordance with theory suggested by experts in cooperative learning, namely; 1) phase (Think) that leads students to think; 2) phase (pair) that leads students to work together and interact with each other; and 3) phase (share) Here students gain meaningful learning experience, they are accustomed to speaking in front of people, so the students who previously shy being personally brave and confident. Student response was very positive towards learning, students were active, enjoy and focus on learning. Cooperative learning arranges as an effort to increase student participation, facilitating students with experience, leadership attitudes and make decisions in groups that helpful for the students' lives outside of school.